(untitled) (Journal of Pharmaceutical Negative Results, 2022)
We extend the research on the distribution of freebies and its impact on the psyche of the voters during elections by first investigating the determinants of manifestoes released by political parties, and then by establishing the association between voting patterns and offering freebies. We take advantage of novel and uniquely reliable data on levels of votes secured by parties within the General elections of 2014 and 2019 to test three hypotheses: first, we expect to see a higher level of voting in favour of parties offering freebies. Second, we hypothesize that there is no significant difference between the groups of the second factor Party in relation to the dependent variable. Third, we argue that because freebies distort institutional incentives, we should observe no association between freebies and the performance of political parties in elections. Our analysis does not ultimately show a meaningful relationship between the supply of economic opportunities and the penetration of relative networks in public institutions. However, our research does support the idea that healthy political rivalry boosts responsibility and lowers levels of state exploitation. We also establish a link between the psyche of voters and its reflection on the results of the election: the penetration of offering freebies goes hand in hand with higher levels of voting in favour of political parties.Through this article, the researchers are trying to investigate all the plausible prospects of offering freebies like economic, social, and legal and also the stand of all stakeholders such as the Supreme Court, the Election Commission, the Central Government, political parties, and the voters and submit their findings supplementing the results with repeating Anova Test for validation of hypotheses.